FREDERIK KORTLANDT: SELECTED WRITINGS ON SLAVIC AND GENERAL LINGUISTICS: Rodopi, Amsterdam/ New York, NY 2011, 470 pp. - Sukač, Roman (Slavia Centralis, 2020)
The paper presents a book by Frederik Kortlandt entitled Selected Writings on Slavic and General Linguistics (2011).
Keywords: Selected Writings on Slavic and General Linguistics; Frederik Kortlandt; Indo-European linguistics; Balto-Slavic linguistics; review